2013
DOI: 10.2196/jmir.2336
|View full text |Cite
|
Sign up to set email alerts
|

Attrition Revisited: Adherence and Retention in a Web-Based Alcohol Trial

Abstract: BackgroundAttrition is a noted feature of eHealth interventions and trials. In 2005, Eysenbach published a landmark paper calling for a “science of attrition,” suggesting that the 2 forms of attrition—nonusage attrition (low adherence to the intervention) and dropout attrition (poor retention to follow-up)—may be related and that this potential relationship deserved further study.ObjectiveThe aim of this paper was to use data from an online alcohol trial to explore Eysenbach’s hypothesis, and to answer 3 resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 43 publications
(47 reference statements)
10
100
3
Order By: Relevance
“…A review of studies showed that theoretical foundation of the intervention, perceived personal relevance to the user, perceived effectiveness, persuasive technologies, credibility and social networking also influence engagement with online interventions. 252 Self-regulatory strategies, such as inviting users to commit to revisiting the intervention (if required), by indicating a time when the user might like to revisit, can be used to enhance exposure. 253 As described in Chapter 3, design features of interventions can also influence engagement.…”
Section: Fidelity Of Digital Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of studies showed that theoretical foundation of the intervention, perceived personal relevance to the user, perceived effectiveness, persuasive technologies, credibility and social networking also influence engagement with online interventions. 252 Self-regulatory strategies, such as inviting users to commit to revisiting the intervention (if required), by indicating a time when the user might like to revisit, can be used to enhance exposure. 253 As described in Chapter 3, design features of interventions can also influence engagement.…”
Section: Fidelity Of Digital Interventionsmentioning
confidence: 99%
“…88 Eysenbach has hypothesised that dropout from a trial usually follows the pattern of non-usage of an intervention, 254 although this was not substantiated in a trial of a website for alcohol harm reduction, in which greater adherence to the intervention was not necessarily associated with greater retention, especially in the intervention arm, and factors associated with intervention usage and retention in the trial were not similar. 252 There is a need to conduct further research to better understand factors influencing retention in trials of digital interventions and engagement with digital interventions. Various strategies can be used to enhance retention in trials of digital interventions, as follows.…”
Section: Retention In Randomised Controlled Trials Of Digital Intervementioning
confidence: 99%
“…Non-usage attrition was assessed in relation to use of more than one intervention component (i.e. use of the PA monitoring system and the website) and this improves upon previous studies which typically assess non-usage attrition in relation to website use only [71,[82][83][84][85][86].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Intervention studies show substantial variability in attrition rates, depending on treatment orientation and clinical severity [43,44]. Generally, drop-out rates are high in populations with alcohol and substance use disorders -ranging from 21-80% [43].…”
Section: Limitations and Mitigation Planmentioning
confidence: 99%